Evaluating the effects of road hump as a traffic calming measure on speed and noise level at a university setting - Mohamed, Mohd Zin; Kadar Hamsa, Abdul Azeez; Mustafa, Nur Asiah; Rosli, Nur Najiah Azhani (International Islamic University Malaysia, 2018)
Traffic speed and noise are the major transport-related determinants in affecting the quality of learning and research environment in a University. The calm and safe environmental set-up of a University is very crucial in creating a conducive learning and research atmosphere on-campus. The increasing number of private vehicles on-campus has resulted in increase in speed and noise level and thus has attributing towards increase in environmental pollution on-campus. Road humps are considered effective as a traffic calming measure in reducing speed and thus noise level of the moving vehicles especially near and middle of the two road humps. However, the imminent reduction in speed of the vehicles depends very much on the profiles of a road hump in terms of its width, length and height. The difference in the profiles of the road hump will cause changing driving behavior of the users especially when approaching a road hump. The road humps with different design profiles are selected to measure the speed and noise level of the vehicles at, before and after each of the selected road humps. Radar speed gun and noise level meters are used to measure speed and noise level of the vehicles at each of designated points along the major circular road in IIUM. Descriptive and fluctuation trend analysis is applied to ascertain the changes in speed and noise level at each of the selected points along the major road in IIUM. The changes in speed and noise level at different selected points at each of the different design profiles of the road humps are the expected findings of this study. The findings stated that road hump profiles affect the speed and noise level of moving vehicle. From that, several recommendations also being highlighted in improving the effectiveness of road humps.